Experimental Studies of Fluid Flow Resistance in a Heat Exchanger Based on the Triply Periodic Minimal Surface - Marcin Kruzel; Krzysztof Dutkowski; Tadeusz Bohdal (Energies)
This study describes experimental data on 3D-printed compact heat exchangers. The heat exchanger is a prototype designed and manufactured additively using 3D printing in metal—AISI 316L steel. The device’s design is based on the triply periodic minimal surface (TPMS) geometry called gyroid, which can only be obtained by incremental manufacturing. This innovative heat exchange surface structure enables these devices to provide higher thermal performance while reducing their weight by up to 50%. Few publications describe thermal or flow tests in this type of device. They mainly concern computer simulations that have yet to be experimentally verified. The authors of this study conducted innovative flow tests to determine pressure drops during the flow of working fluids under conditions of variable temperature, mass flow rate and thermal load. Water was used as a heat transfer fluid during the tests. The range of parameters for the entire experiment was ṁ = 1–24 kg/h; Δp/Δl = 0.05–2 kPa; tcold = 20 °C; thot = 50 °C. Flow characteristics during the single-phase heat exchange process were determined, including Δp/Δl = f(ṁ), Δp/Δl = f(Re), Δp/Δl = f(f). The experimental data will be used to determine the relationships describing flow resistance in structures based on a triply periodic minimal surface, and it also enables one to specify the energy consumption of these devices and compare the profitability of their use to conventional designs, i.e., shell-and-tube or plate heat exchangers.